Kuda ide RP? (Philologia, 2021)
The standard British pronunciation model, long known as Received Pronunciation (RP for short), seems to be changing rapidly, influenced by changes from within as well as from without. The internal phonological changes are those which are considered to be the result of the development of RP. The intrusive /r/ linguistic phenomenon, for example, is seen as the result of RP's internal development. The external changes, like the newly observed ones (Estuary English, for example), originate from other varieties of English. The effects of these two types of influence are examined in this paper, with the primary aim of predicting where 21st century RP is heading to.